A numerical algorithm for modeling laminar flows in an annular channel with eccentricity - Gavrilov, A. A.; Minakov, A. V.; Dekterev, A. A.; Rudyak, V. Ya (Journal of applied and industrial mathematics, 2011)
We propose a numerical algorithm for simulating steady laminar flows of an incompressible fluid in annular channels with eccentricity and rotation of the inner cylinder. This algorithm enables us to describe this class of flows for wide ranges of the annular channel and flow parameters. We present the implementation details and the results of testing this numerical method. For a series of flows in an annular clearance, we compare the numerical results to available analytic solutions and experimental data. In all cases under consideration the simulated data agree well with the available experimental, analytical, and numerical solutions.